Developing A Livelihood Security Index for The Paddy Farmers in Non-Granary Area in Malaysia (S/O 14869) - Ibrahim, Ahmad Zubir; Othman, Zaheruddin; Abdullah Chik, Norlaila; Radin Badaruddin, Radin Firdaus (UUM, 2023)
The main objective of this study is to develop a household livelihoods security index among the paddy farmers in the non-granary area using Livelihood Security Index. Through this index, this study also measures the dimension of food security achievement among paddy farmers using the Sustainable Livelihood Approach. The survey technique with random stratified sampling will be employed, where the structured questionnaires will be distributed to 400 respondents among paddy farmers in the non-granary area in Kedah, Perlis, and Kelantan. Then, the data collected will be analyzed using structural equation modeling(SEM). The outcome of this study is to propose a new measurement of household livelihood security and food security status of paddy farmers in the non-granary area. The outcome will assist policymakers to restructure the social safety net in enhancing Malaysian paddy farmers’ quality of life. Based on the study find out income, Livelihood assets, Livelihood security, personal, security, vulnerability, and water have significant and positive relationships with livelihood security. Also, livelihood security is positive and significant with food security. However, the construct action, community, education, environment, and health show non-significance and positive except health and action construct to the livelihood security construct. The study also found that the index livelihood security among paddy farmers in non-granary areas was a medium-high with score 0.60. The study also to proposes production and livelihood well-being to increase livelihood security among paddy farmers in the non-granary area.